(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: Objective of this study was to compare the post-operative pain after septoplasty with and without nasal packing in patients presenting with nasal septal deformity (NSD). Methodology: This randomized controlled trial was conducted at Department of Otolaryngology Sir Ganga Ram Hospital, Lahore for a duration of one year in the year 2014. One hundred cases of nasal septal deformity were included in the study through Non-Probability Purposive Sampling. The patients were randomly divided into two groups. In group A, 50 patients underwent septoplasty with nasal packing while in group B, septoplasty without nasal packing was done in 50 patients. Postoperative severe pain (visual analogue scale VAS>7) was noted. The collected data was analysed statistically by using SPSS version 16. Both groups were compared for post-operative pain by using chi-square test. P-value <0.05 was considered as significant. Results: In this study, patients in whom packing was done, post-operative severe pain on visual analogue scale(VAS) was noted in 24 (48%) cases while in the non- packing group, post-operative severe pain was noted in10(20%) patients only. Statistically there is a significant difference between the study groups for post-operative pain score (p-value=0.003). Conclusion: Septoplasty without nasal packing has less pain as compared to the one with nasal packing.